Reporting of Sociodemographic Data in Cochlear Implant Clinical Trials: A Systematic Review. Issue 2 (21st February 2023) - Meinhardt, Gerek; Sharrer, Christine; Perez, Nicole; Downes, Alexandra; Davidowitz, Tess; Schuh, Marissa; Robinson, Lauren; Lustig, Lawrence R.; Bush, Matthew
Abstract : Objective: The purpose of this study was to systematically evaluate the literature on the frequency of reporting of sociodemographic data (gender, race, ethnicity, education status, health insurance status, geographic location of residence, and socioeconomic status) among interventional clinical trials involving cochlear implant patients. Databases Reviewed: A systematic search was performed in PubMed, Cochrane Database of Systematic Reviews, Web of Science, and SCOPUS to identify peer reviewed research. Methods: A systematic review was performed, which included original prospective clinical trial research studies involving cochlear implantation and/or interventional trials involving cochlear implant patients. Collected data included funding type, level of evidence, race reporting, ethnicity reporting, socioeconomic status reporting, education level reporting, type of insurance, geographic location, and gender of patients. Results: A total of 644 articles were included for review. Gender was the most reported sociodemographic factor (70% of included studies). Reporting of other data among included studies was low: educational level (6%), socioeconomic status (2%), race (1%), ethnicity (1%), insurance status (0.3%), and geography (1%). The odds of reporting gender (odds ratio [OR] = 1.51), education (OR = 1.81), and geography (OR = 2.72) increased with each subsequent publication date decade; however, this trend was not seen for reporting of race, ethnicity, socioeconomic status, or insurance. The reporting of gender was less likely to be reported in studies with the pediatric participants (OR = 0.62), level II evidence (OR = 0.14), and device programming interventional studies (OR = 0.26). Conclusion: Reporting of sociodemographic data, other than gender, is low among prospective clinical trials involving cochlear implant patients. The lack of reporting of this key data may limit research rigor and generalizability. Clinical researchers are advised to prospectively collect these data to promote equity in cochlear implant research and clinical care.